(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
The device providing aiding individuals with paralysis, who struggle to communicate their needs due to impaired motor coordination. The system facilitates communication by allowing the user to transmit text messages using finger movements, particularly beneficial in situations where direct assistance is unavailable. Leveraging Bluetooth technology, the system detects the tilt direction of the user’s finger to operate effectively, enabling patients to interact with healthcare professionals, therapists, and family members remotely. Moreover, the system incorporates continuous monitoring of vital signs, such as heart rate, crucial for healthcare settings. By integrating a microcontroller and a transmitting module, the system collects and transmits periodic data, ensuring realtime monitoring of the patient’s health status. The received data is decoded and displayed on graphical interfaces accessible via laptops, empowering healthcare providers to oversee multiple cases simultaneously. Furthermore, the system offers functionalities for anomaly detection and status monitoring, enabling prompt intervention in case of any deviations or changes in the patient’s condition. This comprehensive approach enhances the efficiency of healthcare management and ensures timely responses to critical situations. The development of this solution required the creation of a specialized device capable of translating elementary motions into meaningful communication. The device is designed to be discreet, fitting within the user’s clothing or worn on their finger, ensuring comfort and convenience while facilitating seamless communication. In summary, the proposed system addresses the communication challenges faced by individuals with paralysis, offering a reliable and accessible means of interaction. By integrating motion-sensing technology with continuous health monitoring capabilities, the system empowers both patients and healthcare providers, facilitating efficient communication and enhancing patient care in various healthcare settings.